(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article summarizes current data on biological and morphological changes in the skin after laser tattoo and permanent makeup removal. It examines the mechanisms of pigment destruction (photothermal and photoacoustic effects), the primary inflammatory response, dermal remodeling, and structural changes in the epidermis. Key cellular and molecular processes, including the activation of macrophages, cytokines, and matrix metalloproteinases, are analyzed.